Poems - Rossetti, Christina (Saga Egmont, 2022)
Discover the English writer of romantic poems, Christina Rossetti\'s extensive collection with this comprehensive anthology. Spanning \'The Prince\'s Progress\', following the story of a princess awaiting the return of her prince and \'The Goblin Market\', the tale of Laura and Lizzie tempted with fruit by goblin merchants, Rossetti\'s delicate and swift prose is crafted to charm adults and children alike. Dealing with themes of female sexuality, patience and religion, Rossetti\'s \'Poems\' are the perfect companion for fans of the Radio 4 podcast \'In our Time\'